A Survey of Civic Engagement Education in Introductory Canadian Politics Courses - Stephanie Bell; JP Lewis (Canadian Journal for the Scholarship of Teaching and Learning, 2015)
In recent years, the pressure for educators to cultivate civic participation among Canada’s apathetic youth voters has been mounting. Between 1998 and 2007, a national wave of curriculum reform introducing or enhancing civic engagement education occurred at the secondary level. In this study, we explore the role and place of civic engagement in the Canadian university curriculum. We have chosen to focus on curriculum in political science programs because calls to increase civic engagement originated with the goal of increasing participation in voting by young people, and because civic engagement is widely espoused as a central value in the discipline of political science. We report the findings of a national survey of politics instructors and their course syllabi regarding civic engagement as an intended learning outcome. Our analysis of the survey data involved a comparison of instructor responses with the assessment activities identified on their course syllabi. By analyzing the real and imagined audience(s) and purpose(s) of course assignments, we find that students are required to complete assignments that situate them within academic contexts involving academic purposes and audiences. The apparent conflict between civic education outcomes and academic assessment tasks relates to broader conversations about the purposes of political science education and higher education in general.